The Effect of Inflation and Interest Rate Levels on Consumer Credit with Global Economic Policy Uncertainty as Moderating Variable in Indonesia - Dwi Alam Nugroho; Resti Prima; Osly Usman (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the influence of inflation and interest rates (BI Rate) on consumption credit in Indonesia, with global economic policy uncertainty as a moderating variable. This study uses secondary data in the form of monthly time series data from June 2015 to March 2025 published by the Financial Services Authority (OJK), Bank Indonesia, and the Economic Policy Uncertainty Index. Multiple regression analysis was applied to estimate the relationship of each variable, accompanied by normality, multicollinearity, and heteroscedasticity tests, so that it met the requirements for a valid and robust regression. The results of the study show that inflation has a negative and significant influence on consumption credit, while interest rates also have a negative but insignificant influence. Global economic policy uncertainty has proven to be able to moderate the negative influence of inflation on consumer credit, so that the negative impact is weaker when uncertainty is greater. Meanwhile, the role of the moderation of global economic policy uncertainty on the relationship between interest rates and consumption credit does not appear significant. Regression analysis also showed that models that included moderation variables were better able to explain the variation in consumption credit distribution, which reached 51.3%.